The Rhetoric of Death and Discipleship in Premodern Japan Sōchō's Death of Sōgi and Kikaku's Death of Master Bashō - Horton, H. Mack 1952-; Horton, H. Mack 1952- (Book collections on Project MUSE., 2019)
"Socho's Death of Sogi and Kikaku's Death of Master Basho provide information about iconic figures of premodern Japanese literature and their disciples, while themselves manifesting stylistic accomplishment. This book contains translations of both death accounts and introductions to the poets' lives, times, and works"